2022
DOI: 10.1177/15266028221081082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of the Size of Drug-Coated Balloon Therapy on Restenosis Rate in Femoropopliteal Lesions

Abstract: Purpose: Although the size of drug-coated balloons (DCBs) is determined according to the vessel diameter during femoropopliteal (FP)-endovascular therapy (EVT), the measurements of the vessel diameter vary among modalities and its definitions. The aim of this study was to reveal whether the DCB size fitting (1) angiographically-measured lumen diameter (Angio-lumen size), (2) intravascular ultrasound (IVUS)-measured lumen diameter (IVUS-lumen size), or (3) IVUS-measured external elastic membrane (EEM) diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Few large-scale studies have investigated whether postprocedural findings could be associated with restenosis risk after DCB treatment. The restenosis after DCB treatment has been reportedly affected by various factors, including vessel diameter, CTO, and severe calcification [13][14][15] . The MLA was expected to be highly dependent on baseline characteristics, and the present study successfully addressed those confounding influences by using the GPS method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few large-scale studies have investigated whether postprocedural findings could be associated with restenosis risk after DCB treatment. The restenosis after DCB treatment has been reportedly affected by various factors, including vessel diameter, CTO, and severe calcification [13][14][15] . The MLA was expected to be highly dependent on baseline characteristics, and the present study successfully addressed those confounding influences by using the GPS method.…”
Section: Discussionmentioning
confidence: 99%
“…Allan et al conducted an RCT and showed that the use of IVUS results in larger vessel diameter and significant reduction in the restenosis rate 1 year after DCB treatment (9.1% vs. 37.5%, p=0.001) 20) . Furthermore, in a retrospective study, Kurata et al suggested that larger DCB sizes are selected based on EEM diameter than based on lumen diameter (5.2 vs. 4.8 mm), with a 2-year restenosis rate of 19.7% for the EEM-based strategy compared with 33.1% for the lumen-based strategy 15) . These two investigations indicate that selecting sufficiently large balloon sizes might be beneficial to the reduction of restenosis after IVUSguided EVT treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-antiplatelet therapy (100 mg/day aspirin with 75 mg/day clopidogrel or 3.75 mg/day prasugrel) was prescribed for at least 1 week prior to EVT and continued at least 1 month after EVT. 10) Subsequent therapies were at the discretion of the treating physicians. Oral anticoagulation was prescribed in patients with atrial fibrillation, deep vein thrombosis, or previous implantation of a mechanical heart valve.…”
Section: Methodsmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT; aspirin with clopidogrel or prasugrel) was prescribed for at least 1 week before the EVT and continued at least 1 month. 11 When patients had bleeding complications or high bleeding risks, single antiplatelet therapy (SAPT) could be allowed. 4 Subsequent prescription of the antiplatelet therapy was at the discretion of each treating physician.…”
Section: Methodsmentioning
confidence: 99%